Output-Based Aid and Carbon Finance - Bishop, Veronique; Johannes, Lars (World Bank, Washington, DC, 2012)
Out-based aid (OBA) involves the use of explicit, performance-based subsidies to deliver public services such as water and sanitation. It is used to fund the gap between people's willingness or ability to pay for a service whose delivery is deemed worth subsidizing and the cost of providing that service. It can also be used to finance public goods or to mitigate externalities such as environmental costs. One such application is carbon finance, an output-based approach to mitigating climate change. Under the Kyoto Protocol's project-based mechanisms-the Clean Development Mechanism and Joint Implementation-projects in developing and transition economies that reduce greenhouse gas emissions can receive "carbon credits." Carbon revenues can help project sponsors close the financing gap between climate-friendly projects and conventional projects, and can help industrial countries reduce their cost of compliance with the Kyoto Protocol.